Efektifitas Mekanisme Bonding Dividen dan Hutang untuk Mengurangi Masalah Agensi pada Perusahaan di Bursa Efek Jakarta - Zaenal Arifin (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2003)
Jensen (1986) said that the agency problem can be minimized by reducing the free cash flows in a company. These free cash flows can be reduced by increasing the debt or by increasing the dividend. This theory was developed in the United State of America in which most of the listed companies have a dispersed ownership structure. It is interesting to evaluate the effectiveness of this bonding mechanism for the listed companies in Jakarta Stock Exchange in which most of them have a concentrated ownership structure. The purpose of this research is to examine the effectiveness of this bonding mechanism.By investigating the same sample of listed companies in Jakarta Stock Exchange in 1996 and in 2000, this research discovers that in 1996, the debt bonding mechanism is not effective to reduce an agency problem but it increases the agency problem instead. In 2000, the debt bonding mechanism is still not effective but it does not increase the agency problem anymore. Meanwhile, the dividend bonding mechanism is effective to reduce the agency problem both in 1996 and in 2000. However, the dividend bonding mechanism is avoided by the companies that have a family ownership that closed to a minimum portion of majority or domination.Kata Kunci: Agency Problem, Bonding, Hutang, Dividen, Kepemilikan Keluarga